Influence of geocell reinforcement on uplift response of belled piles - Tafreshi, S.N. Moghaddas; Javadi, S.; Dawson, Andrew (Springer, 2014)
Piles are frequently used to transfer the heavy compressive loads to strong soil layers located in the depth of bed. In addition, such piles may be subjected to combination of repeated compressive and tensile loads due to earthquake, wind, etc. This paper describes a series of laboratory model tests, at unit gravity, performed on belled pile, embedded in unreinforced and geocell-reinforced beds. The tests were performed to evaluate the beneficial effect of geocell in decreasing the downward and upward displacements and performance improvement of the uplift response of belled pile under repeated compressive and tensile loads. Pile displacements due to fifty load repetitions were recorded. The influence of the height of geocell above the bell of pile, an additional geocell layer at the base of belled pile, and the number of load cycles on pile displacements were investigated. The test results show that the geocell reinforcement reduces the magnitude of the final upward displacement. It also acts as a displacement retardant, and changes the behaviour of belled pile from unstable response condition due to excessive upward pile displacement in unreinforced bed to approximately steady response condition. Therefore, the geocell reinforcement permits higher tensile loads or increased cycling. The efficiency of reinforcement in reducing the maximum upward displacement of the pile (i.e. pull-out resistance) was increased by increasing the height of geocell above the bell of the pile. Furthermore, the comparison showed that a specific improvement in upward and downward displacement and the stability against uplift can be achieved using an additional geocell layer at the base. The geocell reinforcement may reduce the required length of pile shaft, consequently reducing required excavation, backfill, and pile’s material. Simple dimensional analysis showed the need for an increased stiffness of the geosynthetic components in order to match prototype-scale performance similitude.